Biomechanical analysis of double poling in elite cross-country skiers - Holmberg, H. C.; Lindinger, S.; Stöggl, T.; Eitzlmair, E.; Müller, E. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To further the understanding of double poling (DP) through biomechanical analysis of upper and lower body movements during DP in cross-country (XC) skiing at racing speed.